Contrastes térmicos nocturnos e acumulação de ar frio em áreas urbanas do Sul da Península de Lisboa - Lopes, António (1998)
NOCTURNAL THERMAL PATTERNS AND COLD AIR LAKES IN THE URBAN AREAS OF THE SOUTH OF LISBON PENINSULA - A methodology based on a GIS (Idrisi) is presented in a study in orther to recognise some nocturnal thermal patterns in anticyclonic nights in the south of the Lisbon peninsula. A multiple regression model was used to evaluate which topoclimatic variables are responsible for the thermal variation. The results are presented in table I and figure 5. The areas with high probability of ocurrence of cold air lakes during clear and calm anticyclonic nights were identified. It was estimated that 35% of these suburbs are in the areas where cold air lakes can occur. Night temperatures in the valleys, occupied by urban areas are, on avarage, 1ºC lower than in all the other areas. This leads to an increase of disconfort and cunsumption of energy because these areas have been densely developed and populated in the last decades and the buildings are not usually prepared for cold conditions. Several maps are intended to contribute to the urban planning of Lisbon peninsula.